Development Of Creative Thinking Of Students In The Russian Language Lessons In The Uzbek School - Eshmuradov Shuxrat Xujanovich (Genius Publishing Group, 2023)
The article focuses on the development of creative thinking among students in the Uzbek school during Russian language lessons. The author argues that creative thinking is an essential skill that students should develop to become successful in various areas of life. The article explores different methods and techniques that can be used by teachers to foster creativity in students, such as brainstorming, mind mapping, and problem-solving activities. The author emphasizes the importance of creating a positive learning environment that encourages experimentation and risk-taking to enhance students' creativity. The article concludes that incorporating creative thinking into Russian language lessons can help students develop their cognitive abilities and foster a lifelong love of learning
Keywords: creative thinking; students; russian language lessons